Anaesthesia Management for Pregnant Women Undergoing Laparoscopic Appendectomy: A Descriptive Study (Community Based Medical Journal, 2025)
A cross-sectional, descriptive study was conducted in the Department of Anaesthesiology, Community Based Medical College, Bangladesh (CBMC,B), Mymensingh & three Specialist Private hospital of Mymensingh, Bangladesh, from January 2022 to December 2024, to observe how anesthesia management is operating for pregnant patients undergoing laparoscopic appendectomy. A total of 63 purposively selected pregnant patients were included in this study. Data regarding patients’ age, gestational age, ASA status, anaesthesia techniques, medications, intraoperative and postoperative monitoring, and maternal-fetal outcomes were observed, recorded and analyzed. The mean age of the patients was 26.5±4.2 years; most of them were in their second trimester (58.7%). General anaesthesia with endotracheal intubation was used in 92.1% of cases. Propofol (87.3%) and succinylcholine (100%) were primary agents. Stable haemodynamics were maintained in 88.9% of patients. No major maternal and fetal complications was observed. The mean duration of surgery was 45.2±12.3 minutes, while the mean anesthesia time was 68.5±15.7 minutes and postoperative mean time to extubation was 8.2±3.1 minutes. Average stay in the post-anesthesia care unit was 95.4±22.6 minutes. Our data confirms the safety of general anesthesia for laparoscopic appendectomy in pregnancy, as proper monitoring was ensured. The favorable outcomes support current protocols, though standardized fetal monitoring still remains a bit challenging. Our findings are expected to aid further research on anesthetic management of non-obstetric surgeries in pregnant patients.  CBMJ 2025 July: vol. 14 no. 02 P:28-33